Gods in the City, Gods in the Countryside: Divine Epithets on the Mediterranean Coast of the Tarraconensis - López Gómez, José Carlos (ARYS. Antigüedad: Religiones y Sociedades, 2021)
In this paper I analyse the religious epigraphy from the Mediterranean coast of provincia Tarraconensis with three main targets: firstly, to stablish a classification of the divine epithets attending to the taxonomy created in the framework of the EPIDI project. Secondly, to carry out a differential study focusing on divergencies that may exists between the epithets of urban contexts and those of rural environments. Finally, to develop a study of the worshipers in order to clarify the causes which could have conditioned the election of specific epithets, with the aim of analyse if their action were conditioned by the urban or rural environment where the agents carried out their religious action.